2011
DOI: 10.1103/physreva.84.033828
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the resonance interaction in Mach-Zehnder-Fano interferometers

Abstract: We study tunable interaction of the resonances in the Mach-Zehnder-Fano interferometers (MZFIs). A discrete Mach-Zehnder interferometer (MZI) with balanced arms supports bound states in the continuum. We demonstrate that doping an impurity in conventional MZIs gives rise to robust high-Q Fano resonances with asymmetric line shapes. By means of the modified Fano-Anderson model and the scattering-matrix approach, we show that the transmission and the intensity spectra of the whole system are very sensitive to bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…It should be pointed out that the maximum of the Fano defect's intensity is in between the transmission dip and tip because of the sharp asymmetric line shapes [15]. We emphasize that the resonance ω d is excited due to a symmetry breaking by side-coupled Fano defect [7] and it is not the eigenfrequency of the defect. At the same time, the nonlinear response at ω a is greatly reduced by the step-function like linear transmission compared to resonance ω b and ω c .…”
mentioning
confidence: 82%
“…It should be pointed out that the maximum of the Fano defect's intensity is in between the transmission dip and tip because of the sharp asymmetric line shapes [15]. We emphasize that the resonance ω d is excited due to a symmetry breaking by side-coupled Fano defect [7] and it is not the eigenfrequency of the defect. At the same time, the nonlinear response at ω a is greatly reduced by the step-function like linear transmission compared to resonance ω b and ω c .…”
mentioning
confidence: 82%
“…It is demonstrated that a finite-bandwidth spectrum of perfect reflection appears as the detuning between the photon and atomic frequency varies. It is obvious that when a single photon transport properties can be influenced by the number of atoms that interact with the waveguide as a result of multiple scattering between the propagating photon and the quantum emitters [16][17][18][19][20][21][22][23][24]. In addition to the effects of the collective interaction with the multiple emitters, the coupling modes between atom and the one-dimensional waveguide also affect the photon transport and result in quite involved, nontrivial dispersion relations that can lead to strong reduction of the group velocity of photons [16,17,25], as a consequence of a finite bandwidth.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there have been extensive interests in observing quantum properties of the NAMRs, including optomechanical entanglement [20][21][22], photon blockade [23,24], carrier-envelope phase-dependent effect [25], and optomechanically induced transparency (OMIT) [26][27][28]. By adding more continuum spectra into the Fano resonance system, one can gain more degrees of freedom to manipulate the resonance interaction [32].…”
mentioning
confidence: 99%
“…Moreover, our scheme presents an ideal case to control the Fano resonance of the optomechanical system by using a phase shifter outside the optomechanical system. Furthermore, compared with the conventional Fano profiles exhibiting sharp asymmetric Fano profiles in transmission or absorption [1], the Fano profile in our scheme can be tuned periodically, i.e., from a symmetric line shape [32] to an asymmetric one, and then back to a symmetric one. Inverted Fano profiles can be obtained by properly manipulating the phase shifter.…”
mentioning
confidence: 99%